Deepened snow enhances gross nitrogen cycling among Pan-Arctic tundra soils during both winter and summer. (September 2021) - Xu, Wenyi; Prieme, Anders; Cooper, Elisabeth J.; Mörsdorf, Martin Alfons; Semenchuk, Philipp; Elberling, Bo; Grogan, Paul; Ambus, Per Lennart
Abstract: Many Arctic regions currently experience an increase in winter snowfall as a result of climate change. Deepened snow can enhance thermal insulation of the underlying soil during winter, resulting in warmer soil temperatures that promote soil microbial nitrogen (N)-cycle processes and the availability of N and other nutrients. We conducted an ex situ study comparing the effects of deepened snow (using snow fences that have been installed for 3–13 years) on microbial N-cycle processes in late summer (late growing season) and winter (late snow-covered season) among five tundra sites in three different geographic locations across the Arctic (Greenland (dry and wet tundra), Canada (mesic tundra), and Svalbard, Norway (heath and meadow tundra)). Soil gross N cycling rates (mineralization, nitrification, immobilization of ammonium (NH4 + ) and nitrate (NO3 − ), and denitrification) were determined using a 15 N pool dilution. Potential denitrification activity (PDA) and nitrous oxide reductase activity (N2OR) were measured to assess denitrifying enzyme activities. The deepened snow treatment across all sites had a significant effect of the potential soil capacity of accelerating N cycling rates in late winter, including quadrupled gross nitrification, tripled NO3 − -N immobilization, and doubled denitrification as well as significantly enhanced late summer gross N mineralization, denitrification (two-fold) and NH4 + -N availability. The increase in gross N mineralization and nitrification rates were primarily driven by the availability of dissolved organic carbon (DOC) and nitrogen (DON) across sites. The largest increases in winter DOC and DON concentrations due to deepened snow were observed at the two wetter sites (wet and mesic tundra), and N cycling rates were also more strongly affected by deepened snow at these two sites than at the three other drier sites. Together, these results suggest that the potential effects of deepened winter snow in stimulating microbial N-cycling activities will be most pronounced in relatively moist tundra ecosystems. Hence, this study provides support to prior observations that growing season biogeochemical cycles in the Arctic are sensitive to snow depth with altered nutrient availability for microorganisms and vegetation. It can be speculated that on the one hand growing season N availability will increase and promote plant growth, but on the other hand foster increased water- and gaseous (e.g. N2 and N2 O) N-losses with implications for overall nutrient status. Highlights: Deepened snow enhanced winter nitrification, NO3 − -N immobilization, denitrification. Deepened snow enhanced summer gross mineralization and denitrification. The increases in N cycling rates were driven by the availability of DOC and DON. The effects of deepened snow were most pronounced in wet tundra ecosystems.